DEVELOPMENT, GOVERNANCE, AND SECURITY: A COMPARATIVE STUDY OF SUCCESSFUL AND FRAGILE MODERN STATES - Mišev, Gordana; Stanojević, Petar (The Review of International Affairs, 2026)
In the first quarter of the 21st century, despite all forms of social and other progress, the world has not achieved lasting peace. Social conflict and war, as its worst form, are as old as humanity itself, and it is increasingly evident that they will disappear only when humanity itself disappears. While numerous scientists and the professional public focus on studying conflicts and wars, the study of development, peace and stability has remained on the margins of science. Although there are currently 56 conflicts worldwide, most states are in some form of peace. The research addresses how developed countries secure safety and the extent to which development and security are interrelated. The research focuses on both developed and least-developed countries, examining the factors that drive state development across political, economic, ecological, social and military dimensions, and how these factors are guided through political governance to ensure security at all levels. The aim of the paper is to describe and explain the factors that build peace and influence the security of states. Analysis of various global development reports has indicated that military power, economic development and democracy have an impact, but are not decisive for the peace and security of states. The study concludes that education, particularly a high proportion of highly educated citizens, is the key factor for development, peace and stability.
Keywords: Peace; development; security; interdependence; education